Estimating Ireland’s Tax Elasticities: a Policy-Adjusted Approach - Conroy, Niall (The Economic and Social Review, 2020)
This paper estimates tax elasticities for Ireland. We compile a new dataset on tax policy changes in Ireland. This allows us to use policy-adjusted revenue when estimating tax elasticities. This gives us a cleaner estimate of the relationship between government revenue and its economic drivers. We find that income tax elasticity estimates are significantly above one when policy-adjusted revenue is used, as opposed to significantly below one when unadjusted revenue is used. This highlights the importance of using policy-adjusted revenue when estimating elasticities. We also estimate elasticities of Pay Related Social Insurance and Value-Added Tax, which have previously received little attention in the Irish literature.